BECN1/Beclin 1 sorts cell-surface APP/amyloid β precursor protein for lysosomal degradation. Issue 12 (1st December 2016) - Swaminathan, Gayathri; Zhu, Wan; Plowey, Edward D.
ABSTRACT: The regulation of plasma membrane (PM)-localized transmembrane protein/receptor trafficking has critical implications for cell signaling, metabolism and survival. In this study, we investigated the role of BECN1 (Beclin 1) in the degradative trafficking of PM-associated APP (amyloid β precursor protein), whose metabolism to amyloid-β, an essential event in Alzheimer disease, is dependent on divergent PM trafficking pathways. We report a novel interaction between PM-associated APP and BECN1 that recruits macroautophagy/endosomal regulatory proteins PIK3C3 and UVRAG. We found that BECN1 promotes surface APP internalization and sorting predominantly to endosomes and endolysosomes. BECN1 also promotes the targeting of a smaller fraction of internalized APP to LC3-positive phagophores, suggesting a role for BECN1-dependent PM macroautophagy in APP degradation. Furthermore, BECN1 facilitates lysosomal degradation of surface APP and reduces the secretion of APP metabolites (soluble ectodomains, sAPP). The association between APP and BECN1 is dependent on the evolutionarily conserved domain (ECD) of BECN1 (amino acids 267–337). Deletion of a BECN1 ECD subregion (amino acids 285–299) did not impair BECN1- PIK3C3 interaction, PtdIns3K function or macroautophagy, but was sufficient to impair the APP-BECN1 interaction and BECN1's effects on surface APP internalization and degradation, resulting in increased secretion of sAPPs. Interestingly, both the BECN1-APP association and BECN1-dependent APP endocytosis and degradative trafficking were negatively regulated by active AKT. Our results further implicate phosphorylation of the BECN1 Ser295 residue in the inhibition of APP degradation by AKT. Our studies reveal a novel function for BECN1 in the sorting of a plasma membrane protein for endolysosomal and macroautophagic degradation.